IDENTIFIKASI STRUKTUR BATUAN DAERAH RAWAN LONGSOR DI KECAMATAN CAMBA KABUPATEN MAROS BERDASARKAN METODE GEOLISTRIK KONFIGURASI WENNER - Janna, Nur; Rahmaniah, Rahmaniah; Wahyuni, Ayusari (Universitas Islam Negeri Alauddin Makassar, 2017)
This research was carried out on the Maros-Bone axis road in Sawaru Village, Camba sub-district, Maros district, South Sulawesi. This area is one of the areas prone to ground movement. This is because this area has a hilly and humid geographical condition. To find out the subsurface conditions, a research using the 2-dimensional type geoelectric resistivity method with the Wenner configuration. The results of the analysis and interpretation of the 2-dimensional cross section shows that the Camba sub-district which consists of clay rock, alluvium rock, gravel, compact sedimentary rock, and ground water and the point of dosing is at a depth of 8 meters. This layer has a resistivity value between the resistivity value of 2.71 5,m-5.78 Î©m which is characterized by water-saturated clay rocks and can cause landslides at any time because of the pressure from the top of the rock with a large value of resistivity. The slip plane is marked with clay rock at a depth of 4 meters-8 meters. This type of avalanche is a rotational avalanche.